2018
DOI: 10.1044/2018_jslhr-s-17-0372
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Memory, Inhibition, and Attention in Developmental Stuttering: A Meta-Analysis

Abstract: The present findings were taken to suggest that cognitive processes are important variables associated with developmental stuttering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 133 publications
0
40
0
Order By: Relevance
“…While a growing body of evidence implicates lower accuracy in preschool CWS and AWS compared to TFS on nonword repetition tasks (Bowers et al, 2018;Ofoe et al, 2018), the current challenge is to identify the cognitive processes related to differences in accuracy. Because nonword repetition tasks load a number of cognitive and sensorimotor processes over the course of the task, it is unclear which of these processes may be different in CWS and AWS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a growing body of evidence implicates lower accuracy in preschool CWS and AWS compared to TFS on nonword repetition tasks (Bowers et al, 2018;Ofoe et al, 2018), the current challenge is to identify the cognitive processes related to differences in accuracy. Because nonword repetition tasks load a number of cognitive and sensorimotor processes over the course of the task, it is unclear which of these processes may be different in CWS and AWS.…”
Section: Discussionmentioning
confidence: 99%
“…The task requires listening to and encoding the sounds, holding them in working memory, and then reproducing the sounds in the order in which they were presented. A growing body of evidence implicates load-dependent differences in nonword repetition in both children (CWS) and adults (AWS) who stutter compared to matched controls (Bowers et al, 2018;Ofoe et al, 2018). Recent studies investigating nonword repetition tasks have demonstrated overall lower performance in both preschool CWS (Spencer and Weber-Fox, 2014;Pelczarski and Yaruss, 2016) and AWS (Byrd et al, 2012(Byrd et al, , 2015(Byrd et al, , 2017(Byrd et al, , 2018Coalson and Byrd, 2017).…”
Section: Phonological Working Memory Background and Need For Preliminmentioning
confidence: 99%
“…However, it may be that differences in spontaneous rate are not sufficient to explain this negative mean asynchrony in individuals who stutter. Instead, it could be related to a difference in inhibitory control, which some evidence suggests is affected for both children and adults who stutter . For example, studies by Eggers et al .…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence pointing to deficits in cognitive and metalinguistic skills in children who stutter [ 2 5 ]. CWS have been reported to show weaker executive function (EF; namely, phonological working memory [WM], attentional skills and inhibitory control) relative to children who do not stutter [CWNS; for a review see 6 11 ], with implications for fluency [ 12 , 13 ]. EF is the umbrella term used to describe the abilities needed to manage and allocate cognitive resources during cognitively challenging activities, such as switching between rules or tasks, controlling and focusing attention, ignoring distractions, and inhibiting impulses [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%